EFEKTIVITAS KONSELING MOTIVATIONAL INTERVIEWING UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA BROKEN HOME DI SMP NEGERI 1 PELAIHARI - Anisah, Laelatul; Aminah, Aminah; Farial, Farial (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2020)
Motivation is an important thing in the learning process. The existence of student motivation in learning will make the learning process more enjoyable, communication smoother, reducing student anxiety, increasing creativity and learning activities. Mc. Donald in Sardiman (2008: 73) argues that motivation is a change in energy in a person which is characterized by the appearance of